Rapid reconstitution of functionally active 6-sulfoLacNAc+ dendritic cells (slanDCs) of donor origin following allogeneic haematopoietic stem cell transplant. (4th September 2014) - Mimiola, E; Marini, O; Perbellini, O; Micheletti, A; Vermi, W; Lonardi, S; Costantini, C; Meneghelli, E; Andreini, A; Bonetto, C; Vassanelli, A; Cantini, M; et al.
Summary: The role of dendritic cells (DCs) and macrophages in allogeneic haematopoietic stem cell transplant (HSCT) is critical in determining the extent of graft- versus -host response. The goal of this study was to analyse slanDCs, a subset of human proinflammatory DCs, in haematopoietic stem cell (HSC) sources, as well as to evaluate their 1-year kinetics of reconstitution, origin and functional capacities in peripheral blood (PB) and bone marrow (BM) of patients who have undergone HSCT, and their presence in graft- versus -host disease (GVHD) tissue specimens. slanDCs were also compared to myeloid (m)DCs, plasmacytoid (p)DCs and monocytes in HSC sources and in patients' PB and BM throughout reconstitution. slanDCs accounted for all HSC sources. In patients' PB and BM, slanDCs were identified from day +21, showing median frequencies comparable to healthy donors, donor origin and kinetics of recovery similar to mDCs, pDCs, and monocytes. Under cyclosporin treatment, slanDCs displayed a normal pattern of maturation, and maintained an efficient chemotactic activity and capacity of releasing tumour necrosis factor (TNF)-α upon lipopolysaccharide (LPS) stimulation. None the less, they were almost undetectable in GVHD tissue specimens, being present only in intestinal acute GVHD samples. slanDCs reconstitute early, being donor-derived and functionally competent. The absence of slanDCs from most of the GVHD-targeted tissue specimens seems to rule out the direct participation of these cells in the majority of the local reactions characterizing GVHD.